Transformation of Religious Behavior of Alumni of Islamic Boarding School Students in the Context of Higher Education - Ahmad Andri; Ardi Himawan Atmaja; Berliano Arrasyid; Rodi Wahyudi (MUI Kota Pekanbaru, 2026)
This study examines the transformation of religious behavior among university students who are alumni of Islamic boarding schools (pondok pesantren) after entering the academic context of higher education. Shifts in values, lifestyle, and consistency of worship emerge as prominent phenomena that require scholarly explanation. The purpose of this research is to describe the factors influencing such behavioral transformations and to explore their relevance to social theory. The study employs a qualitative descriptive method, combining library research with questionnaires and online interviews. The findings reveal that campus environment, peer interactions, social media, academic demands, and personal motivation are the primary factors driving the transformation of religious behavior among pesantren alumni in higher education.